Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1073/pnas.1415488112
|View full text |Cite
|
Sign up to set email alerts
|

MmTX1 and MmTX2 from coral snake venom potently modulate GABA A receptor activity

Abstract: GABA A receptors shape synaptic transmission by modulating Cl − conductance across the cell membrane. Remarkably, animal toxins that specifically target GABA A receptors have not been identified. Here, we report the discovery of micrurotoxin1 (MmTX1) and MmTX2, two toxins present in Costa Rican coral snake venom that tightly bind to GABA A receptors at subnanomolar concentrations. Studies with recombinant and synthetic toxin variants on hippocampal neurons and cells expressing common receptor compositions sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 77 publications
1
29
0
1
Order By: Relevance
“…However, examples among pLGICs have remained scarce, with the exception of the reasonably well-characterised interactions of the orthosteric binding site of nAChRs with α-bungarotoxin and conotoxins [74]. A recent breakthrough came from the discovery of the first GABAR-specific toxins from coral snake venom [75], which potently modulate GABA A R activity. Although these particular peptides will likely serve mostly as tool compounds to decipher GABAergic synaptic transmission, they could serve as a starting point to target the dazzling variety of GABA A Rs with more specific therapeutics in the future.…”
Section: Beyond the Agonist-binding Pocket: Discovery Of New Interactmentioning
confidence: 99%
“…However, examples among pLGICs have remained scarce, with the exception of the reasonably well-characterised interactions of the orthosteric binding site of nAChRs with α-bungarotoxin and conotoxins [74]. A recent breakthrough came from the discovery of the first GABAR-specific toxins from coral snake venom [75], which potently modulate GABA A R activity. Although these particular peptides will likely serve mostly as tool compounds to decipher GABAergic synaptic transmission, they could serve as a starting point to target the dazzling variety of GABA A Rs with more specific therapeutics in the future.…”
Section: Beyond the Agonist-binding Pocket: Discovery Of New Interactmentioning
confidence: 99%
“…For other Cys-loop receptors, information about bioactive peptides that target them is scarce. However, the GABA-A receptor should be mentioned here: a decade ago, it was found that one subtype could bind the αBgt51 and it was recently shown that this receptor also binds the αCtx50 and some other snake venom neurotoxins5253. Moreover, although with a low affinity, the GABA-A receptor can bind the α-conotoxin ImI, which interacts with the α7 nAChR50.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, toxins MmTX1 and MmTX2 from coral snake ( Micrurus mipartitus) venom were found to allosterically modulate the GABA A receptor activity, leading to a potentiation of the receptor opening and desensitization by the agonist (Rosso et al . ). In conclusion, the number of receptors, channels, and enzymes targeted by 3FTs is increasing continuously, expanding our knowledge and highlighting the unique capacity of this fold to trigger pleiotropic functions.…”
Section: The Three‐finger Fold Toxinsmentioning
confidence: 97%